0
$\begingroup$

Let F=U $\times$ (U $\times$ x), where x is the position vector and U a uniform vector field. By using the divergence theorem, find the surface integral $\int_S $ F $\cdot$ dS, where S is the closed surface of the cube with verices $(\pm1,\pm1, \pm1)$.

By the divergence theorem $\int_S $ F $\cdot$ dS= $\int_V \nabla \cdot$ F dV.

But now,

$\nabla \cdot F = \nabla \cdot (U \times( U\times x))=(\nabla \times U)(U \times x)-U(\nabla(U \times x))=(\nabla \times U)(U \times x) -U((\nabla \times U)x-U(\nabla \times x))$

Because $U$ is a uniform vector field, I know $\nabla \times U = 0$ and $\nabla \cdot U = 0$, but I'm not sure if $ \nabla \times x=0$, because that would imply $\nabla \cdot F = 0$ and the question wouldn't make sense.

Where am I wrong?

Also, how should I interpret the gradients, $\nabla F$ and $\nabla x$?

$\endgroup$
  • $\begingroup$ Why would $\nabla \cdot F=0$ mean that the question wouldn't make sense? $\endgroup$ – Chappers Apr 12 '18 at 19:31
1
$\begingroup$

It's probably a better idea to expand the double cross product with Lagrange's identity, since we can then forget about cross products altogether: $$ U \times (U \times x) = U(U \cdot x) - x(U \cdot U). $$ Now, $U$ is constant, so any derivative applied to it is zero. The divergence of the second term is simply $-3 \lvert U \rvert^2$. For the former term, it is easiest to use components: $$ \nabla \cdot (U(U \cdot x)) = \partial_i (U_i U_j x_j ) = U_i U_j \delta_{ij} = U_i U_i = \lvert U \rvert^2, $$ so in fact $\nabla \cdot F = -2\lvert U \rvert^2$.


$\nabla F$, when $F$ is a vector field, is a two-index object with components $(\nabla F)_{ij} = \partial_i F_j$ (so $(\nabla x)_{ij} = \delta_{ij}$). It often called a (Cartesian) tensor.


Looking at your calculation, expanding using these identities gives $$ \nabla \cdot (U \times (U\times x)) = (\nabla \times U) \cdot (U \times x) - U \cdot (\nabla \times (U \times x)) \\ = 0 - U \cdot ( U (\nabla \cdot x) - x (\nabla \cdot U) + (x \cdot \nabla) U - (U \cdot \nabla ) x) ) \\ = -3\lvert U \rvert^2 + 0 + 0 + U \cdot (U \cdot \nabla) x. $$ As we noted above, $(\nabla x)_{ij} = \delta_{ij}$, so $(U\cdot \nabla )x = U$, and we get the same answer as before.

$\endgroup$
  • $\begingroup$ I'm a bit confused where my formula went wrong and why it doesn't yield the correct answer, though. Thank you very much! $\endgroup$ – harlem Apr 12 '18 at 20:10
  • 1
    $\begingroup$ @harlem I've added another version of the calculation. I'm not sure what you mean by the $U(\nabla(U \times x))$ term. $\endgroup$ – Chappers Apr 12 '18 at 20:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.